2018
DOI: 10.5137/1019-5149.jtn.24320-18.2
|View full text |Cite
|
Sign up to set email alerts
|

Polyetheretherketone (peek) rods in lumbar spine degenerative disease: mid-term results in a patient series involving radiological and clinical assessment

Abstract: Most important among these are adjacent segment disease (ASD) and pseudoarthrosis (3). Rigid stabilization decreases the range of motion of the spinal column and causes increased stress on the adjacent segments postoperatively. Increased stress on the bone-screw interface also leads to instrumentation problems and pseudoarthrosis (35). Dynamic █ INTRODUCTION S tabilization is sometimes required to relieve the symptoms of degenerative spinal disease. Rigid systems are commonly used to solve these problems. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The VAS score and ODI score significantly improved, which is consistent with the results of previous studies [ 19 , 25 , 27 ]. Sarbello et al [ 35 ] considered that the radiolucency of the PEEK rods might affect the perceptions of the patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The VAS score and ODI score significantly improved, which is consistent with the results of previous studies [ 19 , 25 , 27 ]. Sarbello et al [ 35 ] considered that the radiolucency of the PEEK rods might affect the perceptions of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…The postoperative lordosis of the upper adjacent segment was 10.7°, which was increased by 1.4° to retain the LL. Ogrenci et al [ 27 ] reported the mid-term follow-up results of 172 patients treated with PEEK rods. The average LL was 42.5° preoperatively and 44.0° postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…observed that in 172 patients who underwent PEEK rod instrumentation during an average 2-year follow-up, fusion rates were similar to those in which titanium rods were used according to the literature, but that ASD and other long-term complications were fewer than those in which titanium rods were used, and physiological lumbar movement was better maintained. [ 1 ] Ozer et al . also argued that in 71 patients who were operated on using various dynamic systems, less ASD was shown in follow-ups of at least 2 years compared with rigid systems; moreover, lumbar lordosis and disc height were maintained at a reasonable level.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar spinal stenosis is defined as a clinical syndrome characterized by neurogenic claudication or radicular pain due to the narrowing of the spinal canal or neural foramen and the compression of its neural elements. [ 1 ] The narrowing may be caused by bone hypertrophy, ligament hypertrophy, disc protrusion, spondylolisthesis, or a combination thereof. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%